Pelatihan Menulis Surat Resmi bagi Staf Tata Usaha Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Riau - Alber Alber; Muhammad Mukhlis; Desi Sukenti; Noni Andriyani; Hermaliza Hermaliza; Muhammad Gadink (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2023)
Letters are a means of conveying information or statements in writing to other parties, either on behalf of the person or because of the official or official representative of the sender, to discuss the problem at hand. Knowledge and understanding of letters are certainly very useful for the community. In particular, administrative staff whose job it is to serve students, lecturers, and the academic community related to administration and correspondence Therefore, the Community Service Team, in order to improve the competence of administrative staff, conducted formal letter-writing training activities for administrative staff of FKIP Riau Islamic University. Based on this, the purpose of this service is to provide an understanding regarding the writing of official letters according to the rules that apply to the administrative staff of the Faculty of Teaching and Education, Islamic University of Riau. The method used in this service is a classical and individual approach. Based on the results and discussion, it can be concluded that administrative staff of FKIP Islamic University can write and apply official letters according to the applicable rules, and training in writing official letters for administrative staff of FKIP Islamic University of Riau can be categorized as successful and according to the target.